2019
DOI: 10.3389/fphys.2018.01880
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Four Species of Macro-Algaes as Dietary Ingredients in Litopenaeus vannamei Under Normal Rearing and WSSV Challenge Conditions: Effect on Growth, Immune Response, and Intestinal Microbiota

Abstract: The study was conducted to compare and evaluate effects of four different macro-algaes on growth, immune response, and intestinal microbiota of Litopenaeus vannamei. In the rearing trial 1, shrimp were fed five diets containing four sources of macro-algaes for 8 weeks, named D1 (without macro-algae), D2 (Porphyra haitanensis), D3 (Undaria pinnatifida), D4 (Saccharina japonica), and D5 (Gracilaria lemaneiformis), respectively. Growth performance of shrimp in D5 diet was significantly higher than that of shrimp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…This study showed that the inclusion of M. flexuosa fruit pulp in the diet of L. vannamei had no effect on its growth performance and proximate composition of the muscle. Similar results have been reported by different authors who included plant sources in their experimental diets for L. vannamei, such as the macroalgae Saccharina japonica, Porphyra dioica, Gracilariopsis lemaneiformis, Ulva lactuca and Undaria pinnatifida (Niu et al, 2019;Yang, Xie, Niu, Liu, & Tian, 2017;Yu et al, 2016) and soybean meal (Amaya, Davis, & Rouse, 2007;Sookying & Davis, 2011;Xie, Liu, Zeng, Niu, & Tian, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study showed that the inclusion of M. flexuosa fruit pulp in the diet of L. vannamei had no effect on its growth performance and proximate composition of the muscle. Similar results have been reported by different authors who included plant sources in their experimental diets for L. vannamei, such as the macroalgae Saccharina japonica, Porphyra dioica, Gracilariopsis lemaneiformis, Ulva lactuca and Undaria pinnatifida (Niu et al, 2019;Yang, Xie, Niu, Liu, & Tian, 2017;Yu et al, 2016) and soybean meal (Amaya, Davis, & Rouse, 2007;Sookying & Davis, 2011;Xie, Liu, Zeng, Niu, & Tian, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, the use of diets containing bioactive compound ingredients has gained prominence in L. vannamei aquaculture practices (Niu et al, ; Yang et al, ), with beneficial effects such as improvement in the immune system (Macias‐Sancho et al, ), resistance to temperature stress (Schleder et al, ), increased digestive capacity and greater resistance to white spot syndrome virus infection (Shelder et al, 2018), resistance to hypoxia stress condition (Pakravan, Akbarzadeh, Sajjadi, Hajimoradloo, & Noori, ), improvement in the intestinal antimicrobial activity (Pourmozaffar, Hajimoradloo, Paknejad, & Rameshi, ) and increased antioxidant capacity (Yang, Wu, Jian, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies that have evaluated the effects of different protein sources on the gut microbiota composition of aquatic animal (Zhou et al, 2018;Niu et al, 2019), and previous studies examining P. monodon evaluated the effect of marine invertebrate meals on gut microbiota (Simon et al, 2019). In this study, low dietary FM levels decreased the gut microbial diversity of shrimp and increased the ratio of harmful genera such as Vibrio, Pseudoalteromonas, and Photobacterium, which may be associated with the impaired intestinal health in shrimp.…”
Section: Discussionmentioning
confidence: 77%
“…Similar behavior was observed in L. vannamei when fed diets containing different seaweed species. It was observed that specific seaweeds influenced the increase in Bacteroidetes and the reduction of Proteobacteria in the shrimp intestine (Niu et al, 2019). Some bacterial families, namely Enterobacteriaceae and Aeromonadaceae, both belonging to Gammaproteobacteria class of Proteobacteria phylum, are generally associated with intestinal dysbiosis by reducing the absorption capacity of nutrients (Rigottier-Gois, 2013;Schippa and Conte, 2014).…”
Section: Discussionmentioning
confidence: 99%